2019
DOI: 10.14393/bj-v35n2a20198-41819
|View full text |Cite
|
Sign up to set email alerts
|

Variation of the water table and salinity in alluvial aquifers of underground dams in the semi-arid region of Rio Grande do Norte, Brazil

Abstract: Despite the growing progress in the construction of underground dams, there are few studies to evaluate and monitor these reservoirs after their construction. Thus, a research study was carried out to evaluate the water table level in alluvial aquifers and water salinity in four underground dams selected in the Cobras river basin, Parelhas municipality, Rio Grande do Norte. Water level variation was monitored using the traditional method and the Ground Penetrating Radar with generation of 3D virtual models. Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The same climatological influence was observed by Andrade et al (2012), in the water from alluvial valleys of the semi-arid region of Pernambuco, and by Lima et al (2019), in underground dams located in the Cobra river basin, which covers the municipalities of Parelhas, Carnaúba dos Dantas and Jardim do Seridó, located in the state of Rio Grande do Norte. Andrade et al (2012) warn that the continuous use of water with electrical conductivity above 0.7 dS m -1 in irrigation, without proper management, may contribute to increasing the concentration of salts in the soil.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The same climatological influence was observed by Andrade et al (2012), in the water from alluvial valleys of the semi-arid region of Pernambuco, and by Lima et al (2019), in underground dams located in the Cobra river basin, which covers the municipalities of Parelhas, Carnaúba dos Dantas and Jardim do Seridó, located in the state of Rio Grande do Norte. Andrade et al (2012) warn that the continuous use of water with electrical conductivity above 0.7 dS m -1 in irrigation, without proper management, may contribute to increasing the concentration of salts in the soil.…”
Section: Resultssupporting
confidence: 70%
“…In recent years, the federal government has prioritized funding for the construction of underground dams as a social technology to meet the water needs of the rural population of the semi-arid region (LIMA et al, 2019). This fact can be observed in the state of Rio Grande do Norte, where 1591 underground dams were implemented only by the Technical Assistance and Rural Extension Company of the state (EMATER/RN) between 2008 and August 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture 2023, 13, 2146 2 of 23 In much of the Brazilian semiarid region, producers already suffer from problems related to the availability of good quality water for use in irrigated agriculture [5]. This has caused an increase in groundwater use for irrigation purposes, which generally have high saline contents, with high concentrations of sodium and chlorine in their composition [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported the same climatological effect on water in alluvial valleys in the semiarid region and in underground dams in the agreste region of Pernambuco (ANDRADE et al, 2012;SANTOS;PAIVA;SILVA, 2016), and in underground dams in the Cobra River Basin, in Parelhas, Carnauba dos Dantas, and Jardim do Serido, in the state of Rio Grande do Norte (LIMA et al, 2019b). Electrometric method (Teckna T-1000 pHmeter) Total solids (TS)…”
Section: Resultsmentioning
confidence: 77%